The Application of Police Discretion Authority in Fulfilling Children’s Rights Facing against the Law - Endro Winarno; Muhadjir M Darwin; Warsito Utomo; Supra Wimbarti (Jurnal Penelitian Kesejahteraan Sosial, 2015)
Police as a country agent that most strategically as a distinctive direction in children handling in facing laws. This puts the police personnel in a dilemma between the will to be responsive towards site specific needs and that of the will to make sure that they are able to make and carry out the decision correctly based on valid existing policy. This research is trying to reveal police personnel awareness in managing that dilemma, mainly in the context of understanding and tendency of addressing on the principles of protecting children with factors as a ground in making and carrying out discretional, interpretative, responsive decision in children case investigation. This study applies case study method through observation and interviews to some crime cases investigators that are involving suspected children in Sleman District Police area. This research reveals the understanding towards the principles of protecting children as a ground in addressing the decision making, has eventually not been widely possessed by police investigators. This issue is reflected on the preference domination either on the children protection principles on the handling way or that of its decision making in investigation of children cases. Bureaucratic preference and rule driven that orient to career safety assurance and career developmentare rational choices that base every decision making. This condition becomes one of the factors that make the low level of competency of Bureau personnels and its low bureaucracy conduciveness on the possibility of applying the police’s discretion competency to prioritize the principles of the best interests of the child before involving the society in decision making. The research recommeds integral approach in between criminal policy and social defence policy application to support social welfare policy that implicating on the use of criminal law process as the last alternative, because it hassubsidiary function, that can be used if other alternatives lack of satesfying result. But if it must be used, it should be oriented to protection, sheltering and public service. On this context, police is able to unite two doctrins through different stress in balance, namely a strong hand of society with a soft hand of society.